THE APPLICATION OF THE INDEX CARD MATCH LEARNING METHOD IN IMPROVING READING COMPREHENSION SKILLS IN SLOW LEARNER STUDENTS AT SMP NEGERI 7 SALATIGA - Cristovani Denavia; Dewita Karema Sarajar (Universitas Tribhuwana Tunggadewi, 2024)
Slow learner students tend to have a difficult grasping power, especially towards reading comprehension so instruments are needed to help them in reading comprehension such as the use of Index Card Match. The Index Card Match learning method is a fun designed learning method that is based on matching cards that are usually used by teachers with notes. The purpose of this study was to determine the effect of the application of the Index Card Match learning method in improving the reading comprehension skills of slow learner students at SMPN 7 Salatiga. This research uses the Quasi Experiment method with the experimental design used in this research is One Group Pre-test Post-test Design. Validity measurement in pre-test and post-test questions as a benchmark to determine the effect of treatment is done by conducting expert judgment. This research was conducted in 3 stages, namely Pre-research (preparation and pre-test, Treatment (Treatment) and End of research. The results showed a significance value of 0.012 (p0.05) and a t-count of -2.197, in other words the use of Index Card Match had a significant effect on the learning process.